2011
DOI: 10.1016/j.brainresrev.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin-related protein 1 and mitochondrial fragmentation in neurodegenerative diseases

Abstract: The purpose of this article is to review the recent developments of abnormal mitochondrial dynamics, mitochondrial fragmentation, and neuronal damage in neurodegenerative diseases, including Alzheimer's, Parkinson's, Huntington's, and amyotrophic lateral sclerosis. The GTPase family of proteins, including fission proteins, dynamin related protein 1 (Drp1), mitochondrial fission 1 (Fis1), and fusion proteins (Mfn1, Mfn2 and Opa1) are essential to maintain mitochondrial fission and fusion balance, and to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
253
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(263 citation statements)
references
References 104 publications
7
253
0
3
Order By: Relevance
“…Earlier studies using dominant negative mutant Drp1K38A validated Drp1 as a potential therapeutic target in neurodegenerative diseases. 7 In addition, a very recent study showed that enhanced Drp1 activity caused detrimental mitochondrial fission in Huntington's disease. 27 This study also applied mdiviA, and together with our current findings it is suggested that Drp1 inhibition is a promising approach to prevent mitochondrial fragmentation in different models of delayed neuronal cell death relevant for acute and chronic neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies using dominant negative mutant Drp1K38A validated Drp1 as a potential therapeutic target in neurodegenerative diseases. 7 In addition, a very recent study showed that enhanced Drp1 activity caused detrimental mitochondrial fission in Huntington's disease. 27 This study also applied mdiviA, and together with our current findings it is suggested that Drp1 inhibition is a promising approach to prevent mitochondrial fragmentation in different models of delayed neuronal cell death relevant for acute and chronic neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…6 Mitochondrial fission is mediated by dynamin-related protein 1 (Drp1). [7][8][9] It has been suggested that the outer membrane proteins Fis1 and Mff and the proapoptotic Bcl-2 family protein Bax 10,11 function directly or indirectly as Drp1 receptors to promote mitochondrial fission. The underlying mechanisms that promote and regulate the recruitment of cytosolic Drp1 to mitochondria are largely unknown.…”
mentioning
confidence: 99%
“…Perturbations in mitochondrial dynamics, and altered expression and activity of fission and fusion enzymes has been observed in almost every major neurodegenerative disorder (Table 1), yet it remains unclear precisely how alterations in mitochondrial dynamics contribute to the pathology of these diseases (DuBoff et al, 2013;Hroudová et al, 2014;Reddy et al, 2011;Yu-Wai-Man et al, 2011;Cho et al, 2013;Büeler, 2009). Furthermore, the importance of mitochondrial dynamics has been documented in neuronal development (Li et al, 2004;Dickey and Strack, 2011;Chan, 2006;Ishihara et al, 2009) and survival Merrill et al, 2013;Dagda et al, 2008;Merrill et al, 2011;Cho et al, 2010;Nakamura et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of mitochondrial dynamics to human health is highlighted by studies showing that mutations in Mfn2 and Opa1 underlie neurological disorders, including Charcot-Marie-Tooth disease type 2A and autosomal dominant optic atrophy, whereas a mutation in Drp1 causes neurodevelopmental abnormalities (Alexander et al, 2000;Delettre et al, 2000;Züchner et al, 2004;Waterham et al, 2007). Neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease, and Huntington's disease are also associated with alterations in mitochondrial fusion and division (Cheung et al, 2007;Cho et al, 2010;Kageyama et al, 2011;Reddy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%